Experimental assessment of performance and emissions for hydrogen-diesel dual fuel operation in a low displacement compression ignition engine. Issue 4 (April 2022) - Estrada, L.; Moreno, E.; Gonzalez-Quiroga, A.; Bula, A.; Duarte-Forero, J.
Abstract: The combustion of pure H2 in engines is still troublesome, needing further research and development. Using H2 and diesel in a dual-fuel compression ignition engine appears as a more feasible approach. Here we report an experimental assessment of performance and emissions for a single-cylinder, four-stroke, air-cooled compression ignition engine operating with neat diesel and H2 -diesel dual-fuel. Previous studies typically show the performance and emissions for a specific operation condition ( i.e . a fixed engine speed and torque) or a limited operating range. Our experiments covered engine speeds of 3000 and 3600 rpm and torque levels of 3 and 7 Nm. An in-house designed and built alkaline cell generated the H2 used for the partial substitution of diesel. Compared with neat diesel, the results indicate that adding H2 decreased the air-fuel equivalence ratio and the Brake Specific Diesel Fuel Consumption Efficiency by around 14–29 % and 4–31 %. In contrast, adding H2 increased the Brake Fuel Conversion Efficiency by around 3–36 %. In addition, the Brake Thermal Efficiency increased in the presence of H2 in the range of 3–37 % for the lower engine speed and 27–43 % for the higher engine speed compared with neat diesel. The dual-fuel mode resulted in lower CO and CO2 emissions for the same power output. The emissions of hydrocarbons decreased with H2 addition, except for the lower engine speed and the higher torque. However, the dual-fuel operation resulted in higher NOx emissions than neat diesel, with 2–6 % and 19–48 % increments for the lower and higher engine speeds. H2 emerges as a versatile energy carrier with the potential to tackle current energy and emissions challenges; however, the dual-fuel strategy requires careful management of NOx emissions. Graphical abstract: Image 1 Highlights: Performance and emissions for engine speeds of 3000 and 3600 rpm and torque levels of 3 and 7 Nm. H2 for diesel substitution was generated in an in-house designed and built alkaline cell. Brake Fuel Conversion Efficiency decreases, the impact depending on engine speed and torque. Markedly lower CO and CO2 emissions than neat diesel for the same power output but higher NOx . Abstract : Hydrogen, Diesel engine, electrolyzer, partial substitution, exhaust gases, gas emissions.